IMPLEMENTASI FATWA DSN-MUI NOMOR 89/DSN-MUI/XII/2013 TENTANG REFINANCING SYARIAH PADA BUSSAN AUTO FINANCE (BAF) SYARIAH - Zukhru Fatuzzahro (Fakultas Syariah dan Ekonomi Islam Institut Ilmu Al-Qur'an (IIQ) Jakarta, 2019)
Sharia Refinancing is one of the solutions to the non-performing financing. This study analyzes whether the implementation of Sharia Refinancing in Bussan Auto Finance Sharia is in accordance with the Fatwa DSN-MUI Number 89 Regarding Sharia Refinancing or not. The research method used is a qualitative analytical descriptive method related to research data. Based on the results of this study indicate that the Sharia BAF has run the process of refinancing (sharia refinancing) in accordance with Fatwa DSN-MUI Number 89/DSN-MUI/XII/2013 about Sharia Refinancing, namely using the al bay 'wa al scheme isti`jar.